177. Feasibility of SBRT-VMAT as an alternative to HDR brachytherapy for vaginal cuff. A dosimetric study. (December 2018) - Cilla, S.; Mattiucci, G.C.; Macchia, G.; Deodato, F.; Ianiro, A.; Azario, L.; Morganti, A.G.; Valentini, V.
Abstract: Purpose: We evaluate the role of stereotactic body radiotherapy (SBRT) using VMAT technique as an alternative to high-dose rate brachytherapy (HDR-BRT) in the treatment of vaginal cuff in postoperative endometrial cancer. Methods: CT scans of 5 patients were used in this study. The CTV was defined as the 0.5 cm tissue around the applicator (then subtracting the applicator). Total dose was 30 Gy delivered in 5 fractions. In HDR-BRT, dose was prescribed at a distance of 0.5 cm from the surface applicator. For VMAT diation, a PTV was obtained from CTV by an expansion of 3 mm. Two VMAT plans were generated using a full arc rotation. The first plan was optimized with an anatomy-based optimization module (AB_VMAT) using a 1 mm MLC beam margin to enhance dose fallout. The second plan was generated with a full-inverse planning module (FI_VMAT). Conformity (CI100, CI50), gradient (GI), homogeneity (HI) indexes and equivalent uniform dose (EUD) were calculated. A Kruskal-Wallis ANOVA was performed. Results: VMAT plans provided targets coverage comparable with HDR (p < 0.05). Dose distributions were more heterogeneous with HDR: Dmean were 144.2% for CTV in HDR and 118.0 and 109.1% for PTV in AB_VMAT and FI_VMAT, respectively. The mean values of EUD for CTV were: HDR 40.9 Gy; AB_VMAT 39.0 Gy; FI_VMAT 33.3 Gy. GI indexes were 2.81, 3.37 and 4.15 for HDR, AB_VMAT and FI_VMAT, respectively. Dmean and maximal doses to 2 cc for rectum and bladder were lower in HDR-BRT plans compared to AB_VMAT and FI:VMAT (rectum Dmean: 39.8% vs 47.4% and 53.0%; bladder Dmean: 35.4% vs 40.4% and 46.1%; rectum D2cc: 104.8% vs 108.0% and 116.2%; bladder D2cc: 86.64% vs 94.0% and 100.0%). Conclusions: HDR-BRT provided superior dose distribution with respect to VMAT. AB_VMAT plans tend to better mimic the HDR dose distribution, providing a fast, safe and reasonable alternative.